Changes in place location knowledge: a follow-up study in Arvika, Sweden, 1968 and 2013. Issue 4 (1st October 2016) - Hennerdal, Pontus
ABSTRACT: It has long been understood that widespread place name ignorance exists among the youth of today. The present study compares place location knowledge among students in a Swedish town in 2013 with the knowledge in the same town 45 years earlier. The study used outline maps to determine the ability to locate geographic names. A total of 1, 124 students were included in the study in 2013, and the results are compared with the results from a previous study of 1, 200 students conducted in 1968. The results indicate that contemporary children have improved knowledge of continents and oceans on a world map but have worse knowledge of countries and other locations on a map of Europe. These changes indicate neither a general improvement nor a worsening of place location knowledge but rather an adaptation to contemporary society, in which children travel to and receive news from many parts of the world and in which detailed geographic information is easily obtained.